2004
DOI: 10.1103/physrevb.70.054506
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic properties of a water-vapor-insertedYBa2Cu3O6.5compound studied by NMR, NQR, and

Abstract: We present a detailed NQR, nuclear magnetic resonance (NMR), and SR study of the magnetic phase obtained during a topotactic chemical reaction of YBa 2 Cu 3 O 6.5 high-temperature superconductor with lowpressure water vapor. 65Cu-enriched samples have been used for NQR/NMR studies which allows to get a good resolution in the Cu͑1͒ NQR and Cu͑2͒ zero field NMR (ZFNMR) spectra. It is shown that the NQR spectrum of the starting material transforms progressively under insertion of water, and almost completely disa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The lattice parameters of exposed YBCO correspond to the maximally oxidized state of YBCO [9]. On the other hand, our study has not revealed radical changes in the structure that would be evidence of the transformation of YBCO under the action of absorbed water into the pseudo-YBa 2 Cu 4 O 8 phase, as had been observed in [10], or into another phase. There is ob-served only some change in the phase composition caused by the deposition of the impurity phases.…”
Section: Characterization Of the Initial And Hydrated Ybco By Xrd Andsupporting
confidence: 48%
“…The lattice parameters of exposed YBCO correspond to the maximally oxidized state of YBCO [9]. On the other hand, our study has not revealed radical changes in the structure that would be evidence of the transformation of YBCO under the action of absorbed water into the pseudo-YBa 2 Cu 4 O 8 phase, as had been observed in [10], or into another phase. There is ob-served only some change in the phase composition caused by the deposition of the impurity phases.…”
Section: Characterization Of the Initial And Hydrated Ybco By Xrd Andsupporting
confidence: 48%
“…Now we would like to discuss the possible origin of these internal magnetic fields. We can exclude the presence of the water as a source of the weak antiferromagnetism in the CuO 2 -plane as was suggested recently [25], since our measurements were performed on the fresh samples. Furthermore, the values of the deduced magnetic fields in our case is much larger than those measured in the water-inserted YBaCuO compounds.…”
Section: Deduced Magnetic Fieldsmentioning
confidence: 89%
“…This makes it unlikely there is magnetism stemming from water. 15 Also water appears to enter the sample more easily when the chains are highly ordered leaving large free spaces in the chains. The moments cannot stem from a c-axis component of the sloping background found in the experiment as this does not peak at the magnetic lattice point.…”
mentioning
confidence: 99%